2011
DOI: 10.1021/ja110538b
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Carbon−Halogen Bond Reductive Cleavage in Activated Alkyl Halide Initiators Relevant to Living Radical Polymerization: Theoretical and Experimental Study

Abstract: The mechanism of reductive cleavage of model alkyl halides (methyl 2-bromoisobutyrate, methyl 2-bromopropionate, and 1-bromo-1-chloroethane), used as initiators in living radical polymerization (LRP), has been investigated in acetonitrile using both experimental and computational methods. Both theoretical and experimental investigations have revealed that dissociative electron transfer to these alkyl halides proceeds exclusively via a concerted rather than stepwise manner. The reductive cleavage of all three a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
122
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 140 publications
(124 citation statements)
references
References 66 publications
2
122
0
Order By: Relevance
“…Also omitting the Cu(II) from solution did not provide any polymer layer which means that the polymer is not grown via a homolytic cleavage of the ATRP initiator. It has recently been shown that this is also a possibility induced via an electrochemical reductive process [37]. Though, the XPS-data indicates that the amount of copper in the polymer layer is lower than 0.1%, the presence of it is obvious from a discoloration, which would not result solely from the polymer.…”
Section: Resultsmentioning
confidence: 97%
“…Also omitting the Cu(II) from solution did not provide any polymer layer which means that the polymer is not grown via a homolytic cleavage of the ATRP initiator. It has recently been shown that this is also a possibility induced via an electrochemical reductive process [37]. Though, the XPS-data indicates that the amount of copper in the polymer layer is lower than 0.1%, the presence of it is obvious from a discoloration, which would not result solely from the polymer.…”
Section: Resultsmentioning
confidence: 97%
“…18 In addition, Coote, Guliashvili, and co-workers demonstrated that neither homolytic nor heterolytic bond dissociation applied to the reductive cleavage of C−X in alkyl halides and that a radical anion is not formed during this process, suggesting that the whole SET-LRP mechanism has to be revisited. 276 Although the literature is quite complete for the polymerization in DMSO, the reports regarding aqueous polymerizations are still preliminary and limited. The major difference between DMSO and water is the extent of disproportionation which in the presence of pure water is reported to be ∼100%.…”
Section: Touching the Mechanistic Debatementioning
confidence: 99%
“…160 However, the process requires potentials that are more than 1 V more negative than the standard reduction potential of the alkyl halide, and under such highly reducing conditions, radicals would also be reduced to anions, which is not consistent with the radical mechanism of both SARA ATRP and SET-LRP. 160 To determine if the A comparison of the E p values measured at both electrodes with E o points out that the heterogeneous electron transfer, ET, involves high overpotentials (0.5−1.0 V), typical of ET processes concerted with bond rupture. 160 In addition, E p at Cu is 0.5 V more positive than E p at GC, which is often considered to be the best approximation to an outer-sphere donor, i.e., an electrode acting by an OSET mechanism.…”
Section: Macromoleculesmentioning
confidence: 99%